A shikonin-based hydrogel dressing exhibiting synergistic anti-inflammatory, anti-angiogenic, and anti-fibrotic effects for the prevention of hypertrophic scars - Wang, Ziyu; Zhao, Yujie; Qu, Zhoujiang; Wang, Hui; Zhang, Yuling; Liu, Yufang; Li, Chengde; Wang, Kun; Cao, Guoqi (Frontiers in Immunology, 2026)
IntroductionThe management and prevention of hypertrophic scars present significant challenges in clinical medicine. The development of hypertrophic scars primarily results from angiogenesis, localized inflammatory responses, and the excessive deposition of collagen during the wound healing process. Given the practical requirements for clinical applications, the development of a multifunctional dressing that exhibits synergistic effects and adapts to wounds of diverse shapes is of paramount importance. Hydrogels have emerged as promising biomaterials in dermatological applications due to their excellent biocompatibility, injectability, and strong adhesion. Shikonin (SHI), a compound derived from traditional Chinese medicine, exhibits anti-inflammatory and antioxidant properties that facilitate wound healing. It is posited that SHI possesses diverse pharmacological potential for the prevention and treatment of scars.MethodsBased on these characteristics, this study developed a methacrylated gelatin (GelMA) dressing incorporated with shikonin. In vitro experiments were conducted to evaluate the material properties and biocompatibility of SHI-GelMA. Concurrently, an in vivo rabbit ear model was established to assess the efficacy of SHI-GelMA in inhibiting scar hyperplasia through treatment and subsequent observation.ResultsBy utilizing GelMA’s superior biological properties, the dressing enhances the therapeutic efficacy of SHI on hypertrophic scars while addressing challenges related to drug release kinetics. In vitro experiments demonstrated that the SHI-GelMA dressing exhibits favorable biocompatibility. Importantly, both in vitro and in vivo studies consistently indicated that SHI-GelMA synergistically prevents and inhibits hypertrophic scar formation through SHI's principal anti-inflammatory, anti-angiogenic, and anti-fibrotic mechanisms.DiscussionIn summary, we have successfully developed a functional wound dressing that incorporates the diverse bioactivities of SHI, offering novel materials and strategies for the synergistic prevention and treatment of hypertrophic scars.